The debt bearing capacity of developing countries – a comparative analysis - DE VRIES, B.A. (PSL Quarterly Review, 2014)
The paper looks at “the debt problem” and analyses its extent by taking a closer look at the assessment of the debt bearing capacity of countries. The author considers the economic factors which govern countries’ ability to service loans without impairing their growth or the flexibility of their balance of payments management. A sequence of development stages characterised by countries’ dependence on external capital and the level of debt is then described, and the relevance of this sequence for the assessment of debt bearing capacity is considered. The economic factors underlying the ability to service debt are then discussed and some further problems in the analysis of development debt are considered. Finally, some of the broader aspects of the debt problem are dealt with in the conclusion. JEL: F32, F34